The long-term cure of patients with hereditary medullary thyroid carcinoma: 40 years of follow-up in a single center - Raue, Friedhelm; Bruckner, Thomas; Frank-Raue, Karin (Deutsches Ärzteblatt, 2025)
Background: The cure rate of patients with hereditary medullary thyroid carcionoma (MTC) can be decisively improved by screening for elevated calcitonin (Ctn) levels and RET gene mutations in patients from families affected by multiple endocrine neoplasia type 2 (MEN2), followed by prophylactic thyroidectomy in persons with mutated RET genes. In this long-term observational study, we investigated whether postoperative cures are indeed maintained decades after the procedure. Methods: From 1979 to 2021, 277 patients with MEN2 who underwent thyroidectomy were observed postoperatively for 14.4 +/- 10.3 years (mean, standard deviation). They were classified as either cured or not cured depending on the last measured serum Ctn level (cured, Ctn < 10 pg/mL or < 2 pg/mL; not cured, Ctn >= 10 pg/mL). Depending on their RET mutation status, they were categorized as moderate, high, or highest risk (121, 130, and 26 patients, respectively). Results: 154 patients (55.6%) obtained a long-term cure (Ctn <10 pg/mL). The median age at surgery was 27, 14, and 4 years in patients at moderate, high, and highest risk. All 52 patients who had undergone prophylactic thyroidectomy before the age of 6 years, 9 years, or 6 months had a Ctn level below 2 pg/mL and were cured at the end of the follow-up period. In a multivariable analysis, prognostic factors for a long-term cure were a lower tumor stage and, by tendency, classification as belonging to the moderate as opposed to the highest-risk group. Conclusion: In patients receiving an early diagnosis of MEN2 via family screening, prophylactic thyroidectomy taking into account the RET mutation risk group can achieve a long-term cure of MTC with undetectable serum Ctn levels.
Gesehen am 14.04.2025